2018
DOI: 10.1016/j.jrras.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

234U/238U activity ratios in groundwaters from two aquifers in Saudi Arabia, and correlation with water chemistry

Abstract: The purpose of this study was to determine the activity concentrations of uranium isotopes (234 U and 238 U) and the 234 U/ 238 U activity ratios in groundwater wells from Saudi Arabia. These wells are located in two different regions and tapping different aquifers. The uranium isotopes were measured by alpha spectrometry. The uranium activity ratios (234 U/ 238 U) in the investigated samples had an average value of 1.38 and ranged from 1.0 to 2.17. The relationship between the activity concentrations of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Those reviews support the origin being the direct use of groundwater without pre‐treatment in the arid area far away from the populated residential area in the main cities, where the activities of sheep and camel grazing are widespread in the desert around the residential area of the city. It was documented that, the existence of uranium isotopes in groundwater is related to the hydrothermal, geochemical, and mineralogical conditions of the aquifers 35,36 . Uranium mobility to urinary stones was confirmed in the literature using a gamma spectrometer, and it might have a role in the formation of a specific type of urinary stones 37,38 .…”
Section: Main Results Obtainedmentioning
confidence: 95%
See 1 more Smart Citation
“…Those reviews support the origin being the direct use of groundwater without pre‐treatment in the arid area far away from the populated residential area in the main cities, where the activities of sheep and camel grazing are widespread in the desert around the residential area of the city. It was documented that, the existence of uranium isotopes in groundwater is related to the hydrothermal, geochemical, and mineralogical conditions of the aquifers 35,36 . Uranium mobility to urinary stones was confirmed in the literature using a gamma spectrometer, and it might have a role in the formation of a specific type of urinary stones 37,38 .…”
Section: Main Results Obtainedmentioning
confidence: 95%
“…It was documented that, the existence of uranium isotopes in groundwater is related to the hydrothermal, geochemical, and mineralogical conditions of the aquifers. 35,36 Uranium mobility to urinary stones was confirmed in the literature using a gamma spectrometer, and it might have a role in the formation of a specific type of urinary stones. 37,38 The divalent uranium compounds have the ability to deposit on the surface of hydroxyapatite crystal by ion exchange of Ca +2 ions, and it is strongly bound with two phosphate groups.…”
Section: Uranium In the Urinary Stonesmentioning
confidence: 88%
“…The sample solution was loaded on the UTEVA resin [12]. Uranium was eluted from the UTEVA column using 0.01M HCl, transferred to Teflon beaker [13].…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…In the traditional water quality analysis, regression analysis is often used to determine the correlation between variables. For example, some scholars have used regression analysis to process data on the relationship between activity ratios of 234 U and 238 U and TDS in Saudi groundwater [1]; Mamun and Kwang-Guk also used regression analysis to evaluate the water quality of Yeongsan River in Korea with pollution source analysis and found that the river can be influenced by other systems [2]. Due to the existence of uncertain and nonlinear factors in the data, neural network has become a very popular water quality prediction method with its own good nonlinear mapping ability.…”
Section: Introductionmentioning
confidence: 99%